Establishing Normal Variances and Expectations for Quadriceps Limb Symmetry Index Benchmarks Based on Time from Surgery After Anterior Cruciate Ligament Reconstruction. - Sean Hazzard; Saoirse Connolly; Ashley Wiater; Isabella Sprague; Emily Doolan-Roy; Rachel Lampros; Peter D Asnis (International Journal of Sports Physical Therapy)
The anticipated timeline for muscle strength as well as return to running and sports are some of the most common inquiries by patients undergoing anterior cruciate ligament reconstruction. Despite the popularity of this procedure, the answers to these inquiries are not well described in the literature. The purpose of this study was to evaluate the range of quadriceps strength percentage and function benchmarks at various points after anterior cruciate ligament reconstruction surgery based on sex, age, and graft.